Summary of WG6: Theory and simulations. (July 2020) - Silva, T; Massimo, F; Vieira, J
Abstract: The presentations of working group 6 (theory and simulations) of the fourth edition of the European Advanced Accelerator Workshop presented new ideas for experimental schemes, analytical models, and updates on well-known Particle in Cell codes. New schemes for improving electron beam quality, positron acceleration, ion acceleration, and radiation generation were proposed. Recently developed features of several Particle in Cell codes were also reported.